ASTS: Autonomous switching of task-level strategies - Wang, Xianchang; Lv, Bingyu; Wang, Kaiyu; Zhang, Rui (Zielona Góra: Uniwersytet Zielonogórski)
Autonomous coordination of multi-agent systems can improve the reaction and dispatching ability of multiple agents to emergency events. The existing research has mainly focused on the reactions or dispatching in specific scenarios. However, task-level coordination has not received significant attention. This study proposes a framework for autonomous switching of task-level strategies (ASTS), which can automatically switch strategies according to different scenarios in the task execution process. The framework is based on the blackboard system, which takes the form of an instance as an agent and the form of norm(s) as a strategy; it uses events to drive autonomous cooperation among multiple agents.
Keywords: task-level; autonomous switching strategies; blackboard system; norm